Outcome and Prognosis of Invasive Treatment for Hepatocellular Carcinoma in Very Elderly Patients Over 90 Years Old - Yokoyama, Keiji; Tokushige, Hiroaki; Nagata, Takahiro; Miyayama, Takashi; Shibata, Kumiko; Fukuda, Hiromi; Yamauchi, Ryo; Fukunaga, Atsushi; Takata, Kazuhide; Tanaka, Takashi; et al. (Turkish Journal of Gastroenterology, 2025)
Background/Aims: To evaluate invasive treatment outcomes for hepatocellular carcinoma (HCC) in patients aged over 90 years. Materials and methods: Twenty-six patients were included. Information on backgrounds, course of treatment, outcomes, and changes in Child–Pugh (CP) score and performance status (PS), as well as a comparison of treatment-related complications and 2 year survival after treatment, were retrospectively examined and compared with 311 patients aged under 90 years who were matched under the same conditions. Results: The mean patient age was 91.1 years. Seventeen patients had cirrhosis. The CP score was 7 across all cases. The Barcelona Clinic Liver Cancer stage was B across all cases. The initial treatments were percutaneous local treatment and transcatheter arte rial chemoembolization in 14 and 12 cases, respectively. Several patients with postoperative delirium and cognitive impairment were observed. No significant early post-treatment declines were observed in hepatic reserve and PS. The cumulative survival rates after treatment were 77.8% and 61.5% at 12 and 24 months, respectively. The 2-year survival after treatment for patients aged under 90 years was 87.4% and 75.7% at 12 and 24 months, respectively. No significant difference was observed in treatment-related complica tions or 2-year survival rates between patients aged over and under 90 years. Conclusion: This is the first report to analyze the course of invasive treatment for HCC in patients aged over 90 years. Safety was ensured if hepatic reserve and PS were maintained. The 2-year survival was comparable with that of patients aged under 90 years, suggesting benefit from HCC treatment. Cite this article as: Yokoyama K, Tokushige H, Nagata T, et al. Outcome and prognosis of invasive treatment for hepatocellular carcinoma in very elderly patients over 90 years old. Turk J Gastroenterol. 2025;36(6):381-389.